2019
DOI: 10.1111/apha.13297
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic epoxyeicosatrienoic acid analogue prevents the initiation of ischemic acute kidney injury

Abstract: Aim: Imbalances in cytochrome P450 (CYP)-dependent eicosanoid formation may play a central role in ischemic acute kidney injury (AKI). We reported previously that inhibition of 20-hydroxyeicosatetraenoic acid (20-HETE) action ameliorated ischemia/reperfusion (I/R)-induced AKI in rats. Now we tested the hypothesis that enhancement of epoxyeicosatrienoic acid (EET) actions may counteract the detrimental effects of 20-HETE and prevent the initiation of AKI. Methods: Male Lewis rats underwent right nephrectomy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 77 publications
0
38
0
Order By: Relevance
“…13,14 Renal MRI is noninvasive, affords full kidney coverage, excellent soft tissue contrast, high temporal resolution, and longitudinal studies without ionizing radiation, 15,16 as illustrated by Figure 1 showing multi-parametric MRI for probing different physiological parameters at different spatial scales using T 1 , T 2 , T 2 *, blood oxygenation level dependent, apparent water diffusion and renal blood volume contrast. 13,14 Renal MRI is noninvasive, affords full kidney coverage, excellent soft tissue contrast, high temporal resolution, and longitudinal studies without ionizing radiation, 15,16 as illustrated by Figure 1 showing multi-parametric MRI for probing different physiological parameters at different spatial scales using T 1 , T 2 , T 2 *, blood oxygenation level dependent, apparent water diffusion and renal blood volume contrast.…”
Section: Validation With Quantitative Physiological Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Renal MRI is noninvasive, affords full kidney coverage, excellent soft tissue contrast, high temporal resolution, and longitudinal studies without ionizing radiation, 15,16 as illustrated by Figure 1 showing multi-parametric MRI for probing different physiological parameters at different spatial scales using T 1 , T 2 , T 2 *, blood oxygenation level dependent, apparent water diffusion and renal blood volume contrast. 13,14 Renal MRI is noninvasive, affords full kidney coverage, excellent soft tissue contrast, high temporal resolution, and longitudinal studies without ionizing radiation, 15,16 as illustrated by Figure 1 showing multi-parametric MRI for probing different physiological parameters at different spatial scales using T 1 , T 2 , T 2 *, blood oxygenation level dependent, apparent water diffusion and renal blood volume contrast.…”
Section: Validation With Quantitative Physiological Measurementsmentioning
confidence: 99%
“…Functional MRI of the kidney may serve as a striking example: state-of-the-art renal MRI allows investigators to qualitatively assess physiological parameters such as renal blood flow, GFR and oxygenation. 13,14 Renal MRI is noninvasive, affords full kidney coverage, excellent soft tissue contrast, high temporal resolution, and longitudinal studies without ionizing radiation, 15,16 as illustrated by Figure 1 showing multi-parametric MRI for probing different physiological parameters at different spatial scales using T 1 , T 2 , T 2 *, blood oxygenation level dependent, apparent water diffusion and renal blood volume contrast. Yet, the validity of functional MRI techniques for renal parameters for various (patho-)physiological scenarios remains to be established.…”
Section: Validation With Quantitative Physiological Measurementsmentioning
confidence: 99%
“…2 EETs by contrast are mainly derived from the vascular endothelium, and some may act as vasodilators that attenuate inflammation and hypertension. 1 Notably, at 48-hours follow-up, the EET-treated rats displayed plasma creatinine and urea concentrations and thus creatinine clearance values not different from control rats. 3 The authors exploited previous data showing that (a) modification of the 14,15-EET into a more stable urea bioisostere still yielded potent vascular relaxation, 4 and (b) 14,15-EET is a vasodilator in the perfused kidney.…”
mentioning
confidence: 91%
“…Arachidonic acid can be metabolized by 3 distinct pathways: lipoxygenase, cyclooxygenase and CYPs. The investigators of the Acta Physiologica study 1 have shown previously in mice that deletion of the enzyme responsible for degradation and inactivation of EET, soluble epoxide hydrolase (sEH), elevated EET expectedly but did not exert the predicted protective effect on GFR and tissue injury after 22 minutes kidney ischaemia insult and 2-day follow-up. Both fatty acid derivatives are short lived; they are produced by the kidneys, and substantial data show that 20-HETE is a vasoconstrictor in the renal vascular bed involved in autoregulation of blood flow by myogenic and tubuloglomerular feedback mechanisms and as an amplifier of the vasoconstrictor action of endothelin and angiotensin II (reviewed by Fan and Roman).…”
mentioning
confidence: 99%
See 1 more Smart Citation